Extraction and Phytochemical Composition of Ensete glaucum (Roxb.) Cheesman Fruits in Bu Gia Map National Park, Binh Phuoc Province - Ly, Hai Trieu; Khuong, Huu Thang; Do, Truong Giang; Nguyen, Thi Phuong; Phan, Thi Anh Dao (Journal of Technical Education Science, 2022)
Ensete glaucum (Roxb.) Cheesman fruits have been used in folk medicine to treat kidney stones, diabetes, perforated edema, stomach ulcers, and skin allergies. This study first investigated the phytochemical composition of three parts of E. glaucum fruits collected in Bu Gia Map National Park, Binh Phuoc Province. Results showed that E. glaucum seeds contain flavonoids, saponins, and tannins. Meanwhile, amino acids, flavonoids, and terpenoids were identified in E. glaucum peel; flavonoids, tannins, saponins, and amino acids occur in the pulp. The total content of polyphenols and flavonoids was concentrated in the seeds 59.33 mg GAE/g DW; 70.60 mg CE/g DW), much larger than in the peel (21.09 mg GAE/g DW, 45.43 mg CE/g DW), and pulp (40.75 mg GAE/g DW, 37.82 mg CE/g DW). Until now, the first study researched about general phytochemistry of E. glaucum in Bu Gia Map National Park. Thus, further studies on the chemical compositions and biological effects of E. glaucum fruits should be conducted to develop this medicinal plant.